2010
DOI: 10.1007/s10734-010-9371-1
|View full text |Cite
|
Sign up to set email alerts
|

International doctorates: trends analysis on their decision to stay in US

Abstract: Despite the significant implications of the foreign doctorates' stay or return decision on a personal level, as well as for the home and host countries, there is very little research that provides a comprehensive understanding of the factors that predict international doctorates' decision to stay in the US and how those factors differ by country of origin or field of study. In addition, the patterns of stay (versus return) and the factors influencing those decisions may have changed over time, partly due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 24 publications
1
50
1
Order By: Relevance
“…Cohort-specific patterns varied also by field of study: whilst earlier cohorts in any fields, aside from agriculture, were much more likely to stay than the reference group of biology-graduates, this pattern was reversed for the 2000s cohort, suggesting that conditions for biologists in the USA must have improved relative to those for graduates in other fields. Kim et al (2011) also showed that staying behaviour is partially influenced by financial aspects: being funded as research or teaching assistant during the doctoral studies increased the likelihood of staying afterwards substantially compared to being selfreliant. On the other hand, receiving a fellowship and employer or foreign government financial support lowered the staying probability significantly.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…Cohort-specific patterns varied also by field of study: whilst earlier cohorts in any fields, aside from agriculture, were much more likely to stay than the reference group of biology-graduates, this pattern was reversed for the 2000s cohort, suggesting that conditions for biologists in the USA must have improved relative to those for graduates in other fields. Kim et al (2011) also showed that staying behaviour is partially influenced by financial aspects: being funded as research or teaching assistant during the doctoral studies increased the likelihood of staying afterwards substantially compared to being selfreliant. On the other hand, receiving a fellowship and employer or foreign government financial support lowered the staying probability significantly.…”
mentioning
confidence: 93%
“…Retention rates are especially higher in the field of life sciences (Finn, 2012;Kim et al, 2011;Wolfeil, 2009). …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Soon (2010) reported that nearly half (46%) of international students currently enrolled at two universities in New Zealand had no intention to return to their home countries. International students' decision to return home seems to be influenced by a complex set of push (home country) and pull (host country) factors; however, there is supporting evidence that a reasonably good portion of international students do show intention to stay in the host country after graduation, with varying degrees, depending on the specific sample of international students and their chosen country of study (Kim, Bankart, & Isdell, 2011).…”
Section: Introductionmentioning
confidence: 99%